2019
DOI: 10.3390/ma12111837
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Calcium Aluminates from Non-Saline Aluminum Dross

Abstract: The present work examines the synthesis of tricalcium aluminate (for use as a synthetic slag) from the non-saline dross produced in the manufacture of metallic aluminum in holding furnaces. Three types of input drosses were used with Al2O3 contents ranging from 58 to 82 wt %. Calcium aluminates were formed via the mechanical activation (reactive milling) of different mixtures of dross and calcium carbonate, sintering at 1300 °C. The variables affecting the process, especially the milling time and the Al2O3/CaO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…2 ). The dominance of the C 3 A phase over the mayenite phase in the case of CA40 and CA50 mixes may return to the observed increase of CaO wt% compared to the Al 2 O 3 content in these two mixtures 26 . At 1450 °C, CA40 and CA50 mixes were fully melted, while CA60 and CA70 mixes survived due to their high alumina content.…”
Section: Resultsmentioning
confidence: 81%
“…2 ). The dominance of the C 3 A phase over the mayenite phase in the case of CA40 and CA50 mixes may return to the observed increase of CaO wt% compared to the Al 2 O 3 content in these two mixtures 26 . At 1450 °C, CA40 and CA50 mixes were fully melted, while CA60 and CA70 mixes survived due to their high alumina content.…”
Section: Resultsmentioning
confidence: 81%
“…Aluminum will react with water, resulting in ammonia (NH 3 ), flammable gases (hydrogen (H 2 ), and methane (CH 4 )) [20,21], thereby causing stinky burning and serious harm to groundwater and ecosystems [22][23][24]. According to the studies of C. Y. Lin, F. H. Lu, and Z. Su et al [25,26], the AlN in AD will transfer to Al 2 O 3 when the temperature is higher than 1000 • C. Hence, many studies have investigated sintered calcium aluminate from aluminum dross [26][27][28]. Z. Su et al revealed that a 1.7 molar ratio of Ca/Al roasting for 120 min at 1400 • C under ambient atmosphere would result in high-purity dodecacalcium heptaaluminate (C 12 A 7 ) [26].…”
Section: Introductionmentioning
confidence: 99%
“…Hu et al showed that mixing CaO and secondary aluminum dross in a 0.6:1 (mass ratio) solution resulted in premelted calcium aluminate slag after calcinated at 1723 K for 2 h [27]. F. A. López et al noted that using CaCO 3 and aluminum dross as sources for a 1:3 molar ratio of Ca/Al mixture and sintering at 1300 • C would result in two kinds of calcium aluminate, tricalcium aluminate (C 3 A) and C 12 A 7 [28]. Using aluminum dross in steel melting will benefit two methods.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, some ceramics, refractories, and glasses were successfully prepared based on the chemical compositions of ADW. López et al [16] synthesized calcium alu-minates from the non-saline dross produced during manufacturing metallic aluminum in holding furnaces. Romero et al [17] sintered glass-ceramic tiles by the sinter-crystallization of mixtures composed of aluminum slag and reclaimed packaging glass.…”
Section: Introductionmentioning
confidence: 99%